Synthesis, Characterazation and Antioxidant Activity of Some New Chalcone Derivatives - Batool Kareim Shwesh, Prof. Shetha Fadhil (Drugs and Cell Therapies in Hematology, 2021)
The present study synthesized synthesis and Characterazation with studing Antioxidant activity of Chalcone derivatives. Chalcone [C1] was prepared from reaction of Terephthaldehyde and p-hydroxy acetopheneone. then Chalcone treated with drug contain primary amino group (metoclopramide hydrochloride) to produse schiffe base [C2], At last [C2] reactive with different type of material to configure new derivatives [C3-C8] includes (Tetrazole, Thiazole idenones, Beta-lactam, and Oxazepine).Compounde were characterized by different physico-chemical techniques like, Melting Point, FTIR, 1HNMR. some of these compound have bene screened for their antioxidant activity.